Development of Guided Inquiry-Based E-Modules on Acid and Alkaline Solutions to Improve Critical Thinking Skills and Scientific Attitudes of High School Students - Elmi Royani; Sri Atun (Jurnal Penelitian Pendidikan IPA, 2023)
This development research aims to make and evaluate based on the E-module of guided inquiry on acid and alkaline solution material, knowing the similarities and differences effective contributions between critical thinking skills and student scientific attitudes simultaneously and each before and after the use of the E-module. E-module assessments are carried out by material expert lecturers, media experts, six chemical teachers, and students. E-modules are tested using the pretest-posttest two-group design with the sampling technique, namely simple random sampling in class XI IPA students. The research sample consisted of 36 experimental class students and 34 control class students. The instruments used include critical thinking skills and questionnaires of students' scientific attitudes that are declared valid and reliable using the Rasch model test. The results of students' responses were analyzed using Hoteling's T2 test, while the percentage of effective contributions was known to use the partial Eta Squared value obtained. The results showed the E-module was very well used in learning activities, there were differences in the difference between critical thinking skills and student’s scientific attitudes simultaneously and between experimental classes and controls before and after the use of the E-module, and there was an effective contribution of E-module Against critical thinking skills and student scientific attitudes simultaneously by 24%, to critical thinking skills by 17.4%, and to the scientific attitudes of students by 15.3%.